(untitled) (Nuntius Antiquus, 2013)
One of the axes of the so called “Lucianic Question” is the relationship of the writer from Samosata with the philosophy, and especially with the Cynicism. Even though the idea of a “Cynic Lucian” or a “Philosopher Lucian” has been abandoned, modern criticism still seems to hesitate before the image of the Cynicism that we find in the pages of this author, which fluctuate in a more or less explicit way between the approval and praise in one hand, and the attack and sarcasm in the other. This article seeks to re-examine this issue in the light of an analysis of the figure of the Cynic Alcidamas, a character that appears in the Symposium or The Lapiths. The hypothesis to be defended here is that the seemingly pitiless construction of this Cynic, the most “buffoon” of the guests in the described banquet, actually reveals the sympathy and admiration that Lucian feels about the tradition of which Diogenes of Sinope was the chief representative.